Bias Moderenisasi Pembangunan Dominan pada Proyek Pantai Indah Kapuk Dua (PIK 2): Dampak terhadap Sosial dan Ekonomi Masyarakat - Olivia Fitra Ilma Fadlila Humaida Habib; Andi M. Faisal Bakti (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
The development of Pantai Indah Kapuk 2 (PIK 2) presents serious issues, including eviction, the loss of traditional livelihoods, and the marginalization of local communities within a modernization agenda that disregards social justice and sustainability. This research questions the extent to which the dominant modernization bias influences the socio-economic conditions of the surrounding community, as well as how public participation practices are implemented in the planning and execution of the project. The PIK 2 project has led to social inequality, the deprivation of rights, and environmental degradation, illustrating a pattern of systemic exploitation of coastal communities through the economic and political power of development elites. The dominant development theory framework proposed by Melkote and Steeves is used to examine modernization bias, supplemented by Islamic concepts such as mustadh’afin and ghasab to strengthen the social justice perspective. In this study, the author employs a qualitative case study approach, utilizing in-depth interviews, field observations, and documentation involving affected residents, community leaders, and policymakers. The results of the analysis indicate very low levels of public participation, instances of intimidation during land acquisition, and a significant loss of access to employment and basic facilities for the community. The conclusion of this research emphasizes the need for policy reform to ensure that development is more transparent, participatory, and equitable, in order to protect the rights of local communities from dominant and exploitative development patterns.